A institucionalização da participação comunitária no SUS e a função imunitária do direito - Lutiane de Lara (Universidade do Vale do Rio dos Sinos (UNISINOS), 2016)
This paper analyzes the process of institutionalization of community participation as a collegiate level of the Unified Health System. The Italian philosopher Roberto Esposito’s approach of the Immunization Paradigm has been used as both a theoretical-methodological tool to analyze the relationship between life and law and a strategy to advance in the construction of policies oriented to a common framework. In its approximation to law, the focus of the community experience as a political strategy for struggle and institutionalization in the State has taken the path of negative immunization of the right to health by the State. In such approximation, the community participation enters into the dual universe of the property system and starts generalizing the common of its claim in a sense of public property, i.e. state property. In this sense, we have pointed out a community participation that is not limited to reproducing models, but rather able to disrupt the public/private dichotomy in favor of the notion of common and an affirmative bio-politics.